THE EFFECT OF FINANCIAL RATIOS ON PROFIT GROWTH IN CONSUMER INDUSTRY SECTOR COMPANIES LISTED ON THE IDX - Ravina; Chairil Akhyar; Darmawati Muchtar; Jummaini (Journal of Accounting Research, Utility Finance and Digital Assets, 2024)
The rapid development of the consumer goods industrial sector in Indonesia, especially in an economic context driven by high demand for consumer goods, makes this sector very important for national economic growth. This research aims to analyze the influence of financial ratios on profit growth in consumer industry sector companies listed on the Indonesia Stock Exchange (BEI) for the 2018-2023 period. The variables analyzed include profitability, liquidity, solvency and activity. The research method used is quantitative with a purposive sampling technique, with panel data that combines cross-section and time series data. The research results show that profitability (ROA), liquidity (CR), and activity (TATO) have a positive and significant effect on profit growth, while solvency (DAR) has a negative and insignificant effect. This research provides insight into the importance of managing financial ratios to increase company profit growth in the consumer industrial sector.